“Pregnant’s house” program: a new logic of attention to maternal and perinatal health - Adriano Maçal Pimenta; Juliana Vieira Nazareth; Kleyde Ventura de Souza (Rev Rene)
The program “ House for Pregnant women” is a strategy of the Ministry of Health in Brazil aiming fairness and humanization of assistance for the pregnant women at high risk. It was conducted an epidemiological, transversal, descriptive and exploratory study in the “ House for Pregnant women” of a philanthropic maternity hospital in Belo Horizonte city, aiming to evaluate the impact of this program on maternal health of the 292 pregnant women that used this service and their newborns (NB) . For so, we analyzed data from the registry book of the institution. The results were positive for maternal and perinatal health: clinical improvement of pregnant women who were discharged or evolved to give birth in maternity; high proportion of infants with apgar above 7. The assistance planning and favorable maternal and perinatal indexes show that this program is a good strategy to reduce infant and maternal mortality, Millennium Goals proposed by the United Nations Organization.